The influence of precursors and treatment process on the formation of Iodo-THMs in Canadian drinking water. (1st March 2018) - Tugulea, Anca-Maria; Aranda-Rodriguez, Rocio; Bérubé, Denis; Giddings, Michèle; Lemieux, France; Hnatiw, Joan; Dabeka, Luda; Breton, François
Abstract: The National Survey of Disinfection By-Products and Selected Emerging Contaminants investigated the formation of various disinfection by-products and contaminants in 65 water treatment systems (WTSs) across Canada. Results for six iodo-trihalomethanes (iodo-THMs) are reported in this paper. The participating water treatment systems included large, medium and small systems using water sources and treatment processes which were representative of Canadian drinking water. Five water samples (source water, treated water and three water samples along the distribution system) were collected from each treatment system, both under winter and summer conditions. Samples were stabilized, shipped cold and analysed for six iodo-THMs (dichloroiodomethane–DCIM; dibromoiodomethane–DBIM; bromochloroiodomethane–BCIM; chlorodiiodomethane–CDIM; bromodiiodomethane–BDIM and triiodomethane or iodoform–TIM), using a SPME-GC-ECD method developed in our laboratory (MDLs from 0.02 μg/L for iodoform to 0.06 μg/L for bromodiiodomethane). Concentrations of relevant precursors like dissolved organic carbon (DOC), bromide, iodide and total iodine, as well as other water quality parameters, were also determined. Detailed information about the treatment process used at each location was recorded using a questionnaire. The survey showed that one or more iodo-THMs were detected at 31 out of 64 water treatment systems (WTSs) under winter conditions and in 46 out of 64 WTSs under summer conditions (analytical results from one site were excluded due to sampling challenges). Total iodo-THM concentrations measured during this survey ranged from 0.02 μg/L to 21.66 μg/L. The highest total iodo-THM concentration was measured in WTS 63 where all six iodo-THMs were detected and iodoform was present in the highest concentration. The highest iodo-THM formation was found to occur in treatment systems where water sources had naturally occurring ammonium as well as high bromide, high iodide and/or total iodine concentrations. In two such water systems the total concentration of iodo-THMs exceeded the concentration of regulated THMs. Graphical abstract: Highlights: Iodo-THMs were detected in 45 out of 63 water treatment systems across Canada. In most systems using either chlorine or chloramines, total iodo-THM concentrations were <1 μg/L. Detection frequency was higher in systems using chloramines. Highest concentrations formed when ammonium was present in the water source. Total iodine was the best indicator for the presence of iodinated precursors.